Retail patronage at six to six wardrobe Taman Desa Ilmu, Kota Samarahan / Magdalyne Egan, Ismawi Muhammad and Ismail Abd Jabar - Egan, Magdalyne; Muhammad, Ismawi; Abd Jabar, Ismail (Universiti Teknologi MARA, Sarawak, 2012)
Retailers and other consumer service businesses are continually compelled to make decisions directly towards meeting the varying and changing demands of prospective customers. The more nearly a store's products and services offering meet customers' expectations, the more likely the store will induce customers to become regular patrons. Retailers must also examine and understand the attributes or store characteristics that are most critical in influencing patronage patterns. Basically, the study is to investigate overall sales performance of the company since its opening in November 2011 as well as to identify the customers' shop choice orientation factors towards Six To Six Wardrobe which is located in Kota Samarahan, Sarawak. Since Six To Six Wardrobe is still new in the market and highly depends and focuses on the customer buying volume, it is essential for the management to measure their target customers' overall shop choice orientation factors towards the shop.